- #1

- 5

- 0

1. Give the general solution for the following problem

2. y'=1+x^2+y^2+x^2y^2

3. I have attempted to separate the equation and came up with the following:

y'=1+y^2+x^2(1+y^2) from there I ended up with (y'-y^2-1)/(1+y^2)=x^2

I am stuck on what step to take next. I am sure I am just missing something simple.

2. y'=1+x^2+y^2+x^2y^2

3. I have attempted to separate the equation and came up with the following:

y'=1+y^2+x^2(1+y^2) from there I ended up with (y'-y^2-1)/(1+y^2)=x^2

I am stuck on what step to take next. I am sure I am just missing something simple.

Last edited: